2020
DOI: 10.17576/3l-2020-2601-05
|View full text |Cite
|
Sign up to set email alerts
|

Reading English Academic Texts: Evidence from ESL Undergraduates’ Eye Movement Data

Abstract: Reading English academic texts can be a daunting task for many ESL university students. The complex features of academic texts which include academic discourse, text structure, and vocabulary may affect the reading process. An investigation of how ESL university students read English academic reading materials would provide insights on what learners do to attain comprehension of the text. This study aims to investigate the cognitive processes that take place when ESL undergraduates read English academic texts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Eye tracking measures or indices therefore provide spatial and temporal resolution of visual attention. Higher values in the length and number of fixations could suggest processing or comprehension difficulties (Rayner et al, 2006;Scheiter & Eitel, 2017;Sulaiman et al, 2020).…”
Section: Eye Tracking In Reading Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Eye tracking measures or indices therefore provide spatial and temporal resolution of visual attention. Higher values in the length and number of fixations could suggest processing or comprehension difficulties (Rayner et al, 2006;Scheiter & Eitel, 2017;Sulaiman et al, 2020).…”
Section: Eye Tracking In Reading Researchmentioning
confidence: 99%
“…Furthermore, many of them, regardless of the labels, found the texts difficult mostly because of the unfamiliar and difficult vocabulary. Sulaiman et al (2020) suggested that the vocabulary used in academic texts could implicate text comprehension. Despite acknowledging that readers need adequate vocabulary knowledge to comprehend academic texts, the study did not measure the participants' vocabulary knowledge and establish its link with comprehension of the texts.…”
Section: Eye Tracking In Reading Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology is used in research across different areas of studies, for instance, to examine the processing of literal versus metaphorical expressions in Malay (Tengku & Salehuddin, 2020), graphic novels in English (Mohd Yusof et al, 2020) and science terminologies in Mandarin (Soh, 2017). Local eye-tracking studies have also evolved to incorporate retrospective interview data as a methodological triangulation strategy (Warid Mihat et al, 2018) as exemplified in Sulaiman et al (2020). However, we are not aware of any studies that explore the reading processes of Malaysian ESL learners while reading science texts with graphics.…”
Section: Processing Multiple Representationsmentioning
confidence: 99%
“…According to Zhang (2012) and Amaluddin et al (2018), a strategy -based instruction is important for teachers to use as they help learners develop listening comprehension, and research revealed that good learners used various metacognitive, cognitive, and social strategies, and the less able learners became better when they were taught these strategies (Osada, 2004;& field, 1998). Likewise, Sulaiman et al, (2020) clarified that cognitive strategies, as a part of the strategy-based instruction, are quite significant to learners because the more learners practice them, the more they could recognize texts, make inferences, and eventually understand it thoroughly.…”
Section: Literature Reviewmentioning
confidence: 99%